Phosphogypsum as a soil fertilizer: ecotoxicity of amended soil and elutriates to bacteria, invertebrates, algae and plants - Hentati, Olfa
Phosphogypsum (PG) is a metal and radionuclide rich-waste produced by the phosphate ore industry, which has been used as soil fertilizer in many parts of the world for several decades. The positive effects of PG in ameliorating some soil properties and increasing crop yields are well documented. More recently concerns are emerging related with the increase of metal/radionuclide residues on soils and crops. However, few studies have focused on the impact of PG applications on soil biota, as well as the contribution to soils with elements in mobile fractions of PG which may affect freshwater species as well. In this context the main aim of this study was to assess the ecotoxicity of soils amended with different percentages of Tunisian phosphogypsum (0.0, 4.9, 7.4, 11.1, 16.6 and 25%) and of elutriates obtained from PG – amended soil (0.0, 6.25, 12.5 and 25% of PG) to a battery of terrestrial (Eisenia andrei, Enchytraeus crypticus, Folsomia candida, Hypoaspis aculeifer, Zea mays, Lactuca sativa) and aquatic species (Vibrio fischeri, Daphnia magna, Raphidocelis subcapitata, Lemna minor). Both for amended soils and elutriates, invertebrates (especially D. magna and E. andrei) were the most sensitive species, displaying acute (immobilization) and chronic (reproduction inhibition) effects, respectively. Despite the presence of some concerning metals in PG and elutriates (e.g., zinc and cadmium), the extremely high levels of calcium found in both test mediums, suggest that this element was the mainly responsible for the ecotoxicological effects observed. Terrestrial and aquatic plants were the most tolerant species, which is in line with studies supporting the application of PG to increase crop yields. Nevertheless, no stimulatory effects on growth were observed for any of the species tested despite the high levels of phosphorus added to soils by PG. Given the importance of soil invertebrates for several soil functions and services, this study gives rise to new serious concerns about the consequences of PG applications on agricultural soils.